The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/liv.13194
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hepatitis C virus infection and the risk for diabetes: a community‐based prospective study

Abstract: Chronic HCV infection was associated with an increased risk for diabetes after adjustment for other risk predictors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 30 publications
2
33
0
1
Order By: Relevance
“…Since then, the association between HCV infection and incident diabetes has been widely examined in different populations. Previous studies have confirmed that HCV infection increases the risk of diabetes by 41% to 53% in the non‐transplant population, and 1.55‐ to 2.68‐fold in liver transplant recipients . However, in KTRs, results on the association between HCV infection and NODAT were conflicting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, the association between HCV infection and incident diabetes has been widely examined in different populations. Previous studies have confirmed that HCV infection increases the risk of diabetes by 41% to 53% in the non‐transplant population, and 1.55‐ to 2.68‐fold in liver transplant recipients . However, in KTRs, results on the association between HCV infection and NODAT were conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 In recent years, considerable attention has been paid to hepatitis viruses, especially hepatitis B virus (HBV) and hepatitis C virus (HCV), as well as their extrahepatic effects on glucose metabolism. Results from the non-transplant population suggested a notable association between HCV infection and diabetes, [8][9][10] but the association between HBV infection and diabetes remained controversial. [11][12][13][14][15] However, in a transplant setting, especially in KTRs, consensus regarding the association between hepatitis virus infection and diabetes is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to hepatic diseases, chronic HCV infection was found to cause extrahepatic diseases 4648 . However, less than 15% of chronic hepatitis C patients seek clinical care; thus, the community effectiveness of treatment is approximately 7–11% 49, 50 .…”
Section: Discussionmentioning
confidence: 99%
“…After adjustment, the hazard ratio (HR) for developing DM in viremic patients was 1.63 (95% confidence interval [CI] 1.31–2.02, P < 0.01) . While other studies have not found a relationship between HCV infection and DM risk, a recent meta‐analysis of 34 studies including over 200,000 patients supported this association . Data from the interferon (IFN) era demonstrated that sustained virological response (SVR) was associated with reduced risk of developing insulin resistance, improved glycemic control, and a reduced occurrence of ESRD, ischemic stroke, and acute coronary syndrome in DM patients .…”
Section: Dm and Hcvmentioning
confidence: 99%
“…7 While other studies have not found a relationship between HCV infection and DM risk, a recent meta-analysis of 34 studies including over 200,000 patients supported this association. 8,9 Data from the interferon (IFN) era demonstrated that sustained virological response (SVR) was associated with reduced risk of developing insulin resistance, improved glycemic control, and a reduced occurrence of ESRD, ischemic stroke, and acute coronary syndrome in DM patients. 10,11 More recently, treatment with the IFN free direct-acting antiviral agents (DAAs) has also been associated with better outcomes in HCV-infected patients with DM: improved glycemic control as evidenced by decreased in mean HbA1c, in the use of antidiabetic medications and in insulin had been reported in patients achieving SVR.…”
Section: Dm and Hcvmentioning
confidence: 99%